(untitled) (Scientific journal of the Fergana State University, 2023)
Тhe method of mass spectrometry with inductively coupled plasma was used to study the mineral composition of the plant Prúnus armeníaca L. of the variety "Subkhoniy" growing in the Fergana region. As a result of the analyzes, the qualitative and quantitative content of 26 macro- and microelements in three organs of the plant was determined. The total amount of macronutrients in the leaves is 33825.17 mg/l; in flowers 26311.769 mg/l and in fruits 7570.635 mg/l. The highest content of macronutrients was found for potassium in leaves 22243.325 mg/l and the lowest macronutrient content was found for fruit sodium at 27.972 mg/l. The content of potassium in apricot leaves to the total mass of minerals as a percentage is 65.76%, in flowers 67.7% and in fruits 91.7%. The following trace elements were found in various organs of the plant: Si, Al, Fe, B, Mn, Co, Ni, Cr, Li, Be, and V. Of the toxic elements in the leaves and flowers, 0.001 mg/l of lead was found. Apricot fruits do not contain toxic elements.